Strategies implemented by informal caregivers to facilitate self-care in patients with chronic obstructive pulmonary disease (COPD): a scoping review protocol - Casella, Giovanna; Salemi, Beatrice; Franco, Cosimo; Acampora, Marta; Barello, Serena; Guasconi, Massimo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Chronic obstructive pulmonary disease (COPD) is a disease characterized by persistent respiratory symptoms and airflow limitation. COPD is a significant social and economic burden, and hospital admissions contribute to increased costs. Informal caregivers play a crucial role in supporting COPD patients in their self-care efforts. Therefore, understanding informal caregiver interventions to improve self-care may be helpful in reducing hospitalizations. This is the protocol for a scoping review that aims to map the literature on informal caregiver interventions to facilitate self-care in COPD patients. Research question: What are the strategies implemented by informal caregivers to facilitate self-care for patients with COPD? Methods: The review will adhere to the methodology outlined by the JBI. A comprehensive search strategy will be executed in PubMed, CINAHL, Embase, Web of Science, Scopus, Cochrane, and PsycINFO. Additionally, grey literature and relevant unpublished documents will be searched to minimize publication bias. Studies describing strategies/actions implemented by informal caregivers to promote self-care in COPD patients from all countries will be included. We will exclude abstracts, editorials, articles on paid caregivers and social and healthcare workers. Two independent reviewers will screen titles, abstracts, and full-text articles based on inclusion criteria. Key data from the selected studies will be extracted using a predefined data extraction table. The results will be aggregated into themes and described qualitatively, figures and graphs may also be presented. The results will be presented according to the PRISMA-ScR. Review registration: Open Science Framework https://doi.org/10.17605/OSF.IO/4TWRM